FROM "RED" TO "NEW" CULTURE: TRADITION AND INNOVATIONS IN CHINESE MARXISM - Turenko, Vitalii (Ukrainian Cultural Studies, 2023)
The article examines in detail the understanding of culture and cultural practices in the context of such concepts of Chineseized Marxism as "red culture" and "new culture". It was revealed that culture, as well as aesthetic studies, were in the center of attention of Chinese Marxist circles. Accordingly, within the framework of the idea of "new democracy" the formation and further development of a "new culture" is developed, which involves the preservation of traditional priorities of Chinese civilization and the introduction of new aspects that relate both to the Marxist considerations of the leaders of the CCP and in accordance with modern global trends. Based on this, culture and the cultural revolution are inextricably linked with Marxist projects of criticizing capitalist modernity and building an alternative modernity. In this respect, the various practices and plans of Chinese Marxism are similar to those of Western Marxism. It is substantiated that along with the idea of "new culture" the concept of "red culture" functions, which differs from the former in its containing a synthesis of traditional Chinese culture and an understanding of the latter within the framework of Chineseized Marxism. This, according to thinkers and leaders of the CCP, helps in the fight against cultural imperialism disguised as globalization. Chinese aesthetic scholars followed the Western Marxist agenda; but at the same time deliberately criticized Western Marxism and its Maoist connections. It is noteworthy that the Chinese Marxist experience of the post-revolutionary society and the vision that arose from it drew another cognitive map, an alternative "cultural topology" for modern cultural studies. They offer us an epistemological alternative for understanding the genealogy of critical concepts and conceptual schemes through which the history of modern Chinese culture is interpreted. Chineseized Marxism examines these "topological cultural spaces" from a critical perspective, drawing attention to Chinese theories themselves and juxtaposing these theories with Western Marxist ones so that their assumptions can be subjected to critical scrutiny.